The effectiveness of physiotherapy on pelvic floor muscle function in women with endometriosis: pilot study - Silva, Jeniffer Cristina da; Yonamine, Cristhiane Yumi (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 40 No especial (2024): Prêmio Reynaldo Camargo Neves 2024 e Bolsa Fundação Araucária, 2024)
Endometriosis is a condition in which tissues that normally line the uterus impant in other areas, such as the ovaries, intestines and bladder. The main symptoms include dysmenorrhea, dyspareunia, chronic pelvic pain, difficulties getting pregnant and urinary and intestinal dysfunction. The objetive of this study was to analyze the effects of a kinesiotherapy exercice protocol on pelvic floor muscle function in woman with endometriosis. The research is a pilot study of an uncontrolled clinical trial. Data collection ws divided into three distinct parts: the first, evaluation; the second, intervention; and the third, reevaluation. The tools used were an assesment form, three questionnaires, namely the Quality of Life, Female Sexual Function Index and the Sexual Quotient – Female Version, and the Perineometer to assess pelvic floor muscle strenght and endurance. Subsequenty carrying out a physiotherapeutic protocol, which took place in 20 sessions, three times a week with duration of 60 minutes. The sample consisted of four participants, who had endometriosis, were over eighteen years old and had an active sex life. After completing the physiotherapeutic exercise protocol, it was possible to observe and improvement in all questionnaires applied and in pelvic floor muscle strength.